Die Pentateug tussen deel en geheel - Le Roux, J. H. (Old Testament essays, 2005)
This article focuses on new theories and approaches in the study of the Pentateuch. Since the studies of Gerhard von Rad there is a tendency in the research to take the final form of the text as point of departure. During the past decade some important publications saw the light which should not be ignored by Old Testament scholars in South Africa. Some of them have developed an approach which focuses on the final form of the text. They have often been criticized for 'ignoring' historical developments. However, they may discover that the new theories and approaches are opening up new avenues which will be helpful in the South African context.